Fluid mechanics in SI Units - Hibbeler, R. C. (Pearson Education Limited, 2017)
For Fluid Mechanics courses found in Civil and Environmental, General Engineering, and Engineering Technology and Industrial Management departments. Fluid Mechanics provides a comprehensive and well-illustrated introduction to the theory and application of Fluid Mechanics. The text presents a commitment to the development of student problem-solving skills and features many of the same pedagogical aids unique to Hibbeler texts.